Hyperchaos and Multistability in a Four-Dimensional Financial Mathematical Model - Rech P.C.* (2021)
©2021 L&H Scientific Publishing, LLC. All rights reserved.In this paper we report on hyperchaos and multistability in a fourdimensional nonlinear dynamical system, namely a financial system modeled by a set of four first order ordinary differential equations, whose dynamical behavior is defined by five control parameters. An arbitrarily chosen cross-section of its five-dimensional parameterspace is used to prove numerically the occurrence of both phenomena, multistability and hyperchaos, in the system. Basins of attraction of periodic and chaotic attractors are presented, as well as some typical phase-space portraits.